Pengaruh Citra Merek, Kepercayaan Merek Dan Kualitas Produk Terhadap Keputusan Pembelian Sunlight di Kecamatan Kateman - Sherry Sherry; Heryenzus Heryenzus (eCo-Buss, 2022)
The aims of this study are to: (1) determine the effect of brand image on purchasing sunlight in Kateman sub-district. (2) to find out the influence of brand trust on the purchase decision of Sinlight in Kateman sub-district. (3) to determine the effect of product quality on purchasing decisions of sunlight in Kateman sub-district. This research is a quantitative research conducted in Kateman Subdistrict, precisely in Guntung River, Indragiri Hilir Regency, Riau on 183 respondents. The analysis test was done by using multiple linear regression test. The result of this research is that the brand image variable has a value of 0.000 < 0.05 so that there is a positive and significant influence of brand image on sunlight purchasing decisions in Kateman District. In the brand trust variable the value is 0.11 < 0.05 so that brand trust has a negative and significant influence on sunlight purchasing decisions in Kateman District. The product quality variable has a value of 0.00 < 0.05 so that there is a positive and significant effect on product quality on purchasing decisions for sunlight in Kateman District. On brand image, brand trust, and product quality if tested together or simultaneously have a positive effect on purchasing decisions. This means that brand image, brand trust and product quality that are continuously improved with new innovations will make purchasing decisions increase in a positive direction